2006
DOI: 10.1007/s10526-006-9062-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Beauveria species from Lebanon and evaluation of its efficacy against the cedar web-spinning sawfly, Cephalcia tannourinensis

Abstract: Larvae of the cedar web-spinning sawfly, Cephalcia tannourinensis Chevin (Hymenoptera: Pamphiliidae), infected with a white fungus were collected from the Tannourine-Hadath El-Jebbeh cedar forest. Macro-and micro-morphological data based on the examination of colonies, conidiophores, and conidial shape of the fungus suggested a Beauveria species. Sequence analysis of the internal transcribed spacer regions of the isolated fungus showed that it is most closely related to isolates of B. bassiana Clade C. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…Isolation of these fungi have been based on insect cadavers or soil (Zimmermann 1986;Abdo et al 2008;Glare et al 2008). Both two methods with a susceptible insect host and selective media have been utilized to the isolation of EPF from soil (Zimmermann 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of these fungi have been based on insect cadavers or soil (Zimmermann 1986;Abdo et al 2008;Glare et al 2008). Both two methods with a susceptible insect host and selective media have been utilized to the isolation of EPF from soil (Zimmermann 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, B. bassiana was the most frequent detected fungus in rice collected from fields similar to others studies that have shown B. bassiana as the most widespread entomopathogenic fungi in the endemic Moroccan forests of Argania spinosa , Switzerland, Spain, China and Southern Italy [ 22 , 47 , 48 , 49 , 50 ]. Moreover, B. bassiana has been reported as the major pathogen of insects in more than 200 species that have been identified from the soil and dead insects in nature [ 24 , 25 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exogenous isolates of the entomopathogenic fungi that were commercialized as pest biocontrol agents in different countries may be ineffective on some pests due to environmental suitability and strain differences related to the host [ 24 ]. Therefore, the application of local isolates may be a promising choice mainly in case of ecological suitability with pest species and lower hazards on non-target organisms compared to exotic strains [ 22 , 25 , 26 , 27 ]. These points were verified by several studies that demonstrate the virulence of isolates belonging to the same fungal species could be different because of genetic variations occurring in a specific geographical distribution [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…În condiții de laborator s-a observat că tratarea larvelor cu spori de B. bassiana determină moartea lor la fel de relativ rapid ca și în cazul tratării cu I. farinosa (Markova 2000). Tot în condiții de laborator, o sușă de B. bassiana izolată din Liban s-a dovedit a fi mai eficientă decât Dimilin SC48 când s-a aplicat asupra ouălor sau larvelor (L1-L3) de Cephalcia tan nourinensis Chevin 2002, lăsând să se între-vadă posibilitatea utilizării acestei ciuperci în combaterea defoliatorului în stadiu de larvă activă (Abdo et al, 2008). Actualmente există numeroase produse comerciale pe bază de B. bassiana (Jaronski 2014), dar nu se cunosc experimente de teren în care asemenea produse să fi fost testate împotriva larvelor sau nimfelor de C. abietis.…”
Section: Oleniciunclassified